2020
DOI: 10.28932/jmh.v2i6.2763
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of Intratemporal Complication in Chronic Suppurative Otitis Media Patient with and without Cholesteatoma at Hasan Sadikin General Hospital Bandung

Abstract: Otitis media supuratif kronis (OMSK) merupakan penyakit telinga umum di negara-negara berkembang. Kasus OMSK dengan kolesteatoma sering disebut sebagai tipe bahaya. Tujuan penelitian ini untuk mengetahui karakteristik komplikasi intratemporal pada pasien OMSK dengan dan tanpa kolesteatoma di Poliklinik Telinga Hidung Tenggorok Bedah Kepala Leher (THT-KL) Rumah Sakit Hasan Sadikin (RSHS) Bandung. Penelitian ini merupakan penelitian deskriptif retrospektif dari pasien yang datang ke poliklinik THT-KL RSHS Bandun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…20 Martanegara et al (2020) noted a significant male predominance at 66.84%. 21 Conversely, Nugroho et al (2013) observed a twofold higher prevalence in women compared to men. These studies suggested no significant gender-based disparities, aligning with the results as no significant distinctions were observed based on gender characteristics.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…20 Martanegara et al (2020) noted a significant male predominance at 66.84%. 21 Conversely, Nugroho et al (2013) observed a twofold higher prevalence in women compared to men. These studies suggested no significant gender-based disparities, aligning with the results as no significant distinctions were observed based on gender characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…This age group appears particularly susceptible to CSOM, likely due to their productive age and potentially lower attention to hygiene, sanitation, as well as overall health. 21 Natarajan et al's study (2014) reported different results, with CSOM most commonly occurring in children under 10 years old. This could be attributed to inadequate diet and nutrition in the age group, which weakens the immune system, damages mucosal tissues, and hinders growth and development in children.…”
Section: Discussionmentioning
confidence: 97%